Anti-crack concrete and preparation method thereof
By using lightweight aggregate, water reducer, nano silica and composite fiber materials in concrete, the preparation of crack-resistant concrete is solved, and the problems of high cost of traditional concrete and low strength of lightweight concrete are achieved, and concrete with high strength, high toughness and excellent crack-resistant properties are suitable for projects with multifunctional and high performance requirements.
Patent Information
- Application Number
- CN202510154833.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-12
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional concrete materials are costly and have low strength and are prone to cracking, which limits their application in situations where high stress and high durability are required.
Crack-resistant concrete is prepared by the coordinated combination of raw materials such as light aggregate, water reducing agent, nano-silica and composite fiber materials in the concrete. The method includes adding carbon fiber fabric and stainless steel fibers to the raw material system, and optimizing the internal structure of the concrete through specific aggregate particle size distribution and the addition of nanosilicon dioxide.
It significantly improves the tensile strength and toughness of concrete, improves crack resistance, extends the service life of the structure, and reduces the cost of concrete. It is suitable for harsh environments such as marine engineering and chemical plants.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete, and in particular relates to crack-resistant concrete and a preparation method thereof. Background Art
[0002] Although traditional concrete materials are widely used, their high cost has always been a major challenge facing the construction industry. At present, lightweight concrete is an ideal choice for reducing building loads and improving construction efficiency, but it has significant defects such as insufficient strength and easy cracking, which limits its application in high-stress and high-durability applications. These problems mainly include weak interfacial adhesion between lightweight aggregates and cement matrix, strength loss due to high porosity, and insufficient crack resistance caused by the brittleness of the material itself and poor deformation resistance.
[0003] Therefore, the lightweight concrete in the prior art still has problems such as low strength. Summary of the invention
[0004] The invention provides a crack-resistant concrete and a preparation method thereof, which are used to solve the problems of high concrete cost and low strength of lightweight concrete.
[0005] In a first aspect, the present invention provides a crack-resistant concrete, wherein the raw material system of the crack-resistant concrete comprises, by mass, 160-200 parts of water, 350-500 parts of cement, 600-800 parts of aggregate, 3.5-6 parts of water reducer, 3.5-7 parts of nano-silicon dioxide, 10-20 parts of carbon fiber fabric, 15-30 parts of stainless steel fiber and 3.5-7 parts of antifreeze agent; the density of the aggregate is 340-690 kg / m 3 .
[0006] Compared with the prior art, the beneficial effects of the present invention are as follows: through the coordinated combination of raw materials such as lightweight aggregate, water reducing agent, nano-silica and composite fiber materials, the tensile strength and toughness of concrete can be significantly improved, and the inherent defects of poor tensile performance of concrete can be compensated. It can not only effectively inhibit the plastic shrinkage and drying shrinkage cracks of concrete, but also improve the crack resistance and extend the service life of the structure; and it also has excellent corrosion resistance, is suitable for harsh environments such as marine engineering and chemical plants, further enhances the durability of concrete, and reduces the cost of concrete at the same time.
[0007] Further, the carbon fiber fabric has 1 to 3 layers; and / or, The carbon fiber fabric comprises carbon fiber threads, wherein the carbon fiber threads are twisted together from 2000 to 4000 carbon fibers; and / or, The length of the stainless steel fiber is 20-50 mm, and the diameter is 0.2-0.3 mm.
[0008] Further, the carbon fiber fabric is a twill structure; and / or, The carbon fiber has a length of 9-12 mm, a diameter of 7-10 μm, and an area density of 300-900 g / m 3 .
[0009] Furthermore, the carbon fiber fabric is a 2 / 1 twill structure.
[0010] Furthermore, the aggregate includes expanded perlite and ceramsite; the mass ratio of the expanded perlite to the ceramsite is (30-50): (50-70).
[0011] Further, the mass ratio of the cement, the expanded perlite and the ceramsite is 4:1:3.5; and / or, The mass percentage of the nano silicon dioxide in the raw material system is 2%; and / or, The mass percentage of the water reducing agent in the raw material system is 1.5%; and / or, The mass percentage of the stainless steel fiber in the raw material system is 2.5%, and the volume percentage is 0.5-1.5%; and / or, The mass percentage of the antifreeze agent in the raw material system is 0.5%.
[0012] Further, the particle size of the expanded perlite is 1-5 mm; and / or, The particle size of the ceramsite is 1 to 10 mm; and / or, The particle size of the nano silicon dioxide is 12-30 nm.
[0013] Further, the water reducer includes at least one of a polycarboxylate-based water reducer or a sulfonate-based water reducer; and / or, The antifreeze agent includes at least one of a calcium salt antifreeze agent, a silicate antifreeze agent or a polycarboxylic acid antifreeze agent.
[0014] In a second aspect, the present invention provides a method for preparing crack-resistant concrete, which is used to prepare the crack-resistant concrete described in the first aspect, comprising the following steps: (1) mixing a raw material system including cement, aggregate, nano-silicon dioxide, water, a water reducing agent, an antifreeze agent and stainless steel fiber to obtain a slurry concrete; (2) The slurry concrete is poured to obtain a slurry concrete layer, and a carbon fiber fabric is laid on the surface of the slurry concrete layer; the pouring and laying processes are repeated 1 to 3 times to obtain the crack-resistant concrete.
[0015] Furthermore, the laying process also includes applying an adhesive to the surface of the carbon fiber fabric. DETAILED DESCRIPTION
[0016] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0017] In a first aspect, the present invention provides a crack-resistant concrete, wherein the raw material system of the crack-resistant concrete comprises, by mass, 160-200 parts of water, 350-500 parts of cement, 600-800 parts of aggregate, 3.5-6 parts of water reducer, 3.5-7 parts of nano-silicon dioxide, 10-20 parts of carbon fiber fabric, 15-30 parts of stainless steel fiber and 3.5-7 parts of antifreeze agent; the density of the aggregate is 340-690 kg / m 3 .
[0018] Among them, the aggregate density is 340~690kg / m 3 The lightweight aggregate significantly reduces the density of concrete. The lightweight characteristics of carbon fiber fabrics are highly consistent with the design concept of lightweight concrete, which can further reduce the deadweight of the structure and is suitable for large-span, high-rise buildings and projects that are sensitive to deadweight. The added water reducer and nano-silica increase the strength and durability of concrete. The 28d compressive strength of the concrete reaches 46.6MPa, while reducing the cost of concrete, which is 6% lower than the common lightweight concrete on the market. The addition of carbon fiber fabrics and stainless steel fibers further improves the crack resistance of concrete, significantly enhances the tensile strength and flexural strength, while improving toughness and enhancing impact resistance. The addition of antifreeze enhances the durability of concrete, making it more crack-resistant and environmentally friendly.
[0019] The crack-resistant concrete provided by the present invention can significantly improve the tensile strength and toughness of concrete through the coordinated combination of raw materials such as lightweight aggregate, water reducing agent, nano-silica and composite fiber materials, and make up for the inherent defect of poor tensile performance of concrete. It can not only effectively inhibit the plastic shrinkage and drying shrinkage cracks of concrete, but also improve the crack resistance and extend the service life of the structure; it also has excellent corrosion resistance, is suitable for harsh environments such as marine engineering and chemical plants, further enhances the durability of concrete, and reduces the cost of concrete.
[0020] Furthermore, the carbon fiber fabric has 1 to 3 layers; the carbon fiber fabric includes carbon fiber threads, and the carbon fiber threads are formed by twisting and bundling 2000 to 4000 carbon fibers.
[0021] Carbon fiber has high strength and high modulus, which can significantly improve the tensile strength and toughness of concrete, significantly increase the contact area with concrete, effectively improve the adhesion between carbon fiber and concrete, enhance the ability of the interface to transfer stress, avoid fiber agglomeration, and improve the consistency of the reinforcement effect.
[0022] In a specific embodiment, the length of the stainless steel fiber is 20-50 mm, the diameter is 0.2-0.3 mm; the length of the carbon fiber is 9-12 mm, the diameter is 7-10 μm, and the area density is 300-900 g / m 3 .
[0023] By further limiting the size of stainless steel fibers, the high strength of carbon fibers and the toughness of stainless steel fibers can be further improved. The combined effect can significantly improve the fatigue resistance of concrete and the impact resistance of concrete. Carbon fibers have significant tensile and bending effects, and stainless steel fibers can effectively resist the expansion of cracks, thereby improving the crack resistance, corrosion resistance and ease of processing of concrete.
[0024] Furthermore, the carbon fiber fabric has a twill structure; furthermore, the carbon fiber fabric has a 2 / 1 twill structure.
[0025] The twill fabric formed by warp and weft can further maintain the excellent mechanical and thermal properties of carbon fiber. The high elongation in a specific direction in the twill structure enables the carbon fiber fabric to maintain good performance under high tensile strains of up to 15%, while maximizing the significant thermal properties of carbon fiber, increasing heat transfer efficiency by 100%, and effectively achieving heat transfer control.
[0026] Optionally, the aggregate includes expanded perlite and ceramsite; the mass ratio of the expanded perlite to the ceramsite is (30-50):(50-70).
[0027] The use of expanded perlite and ceramsite compound can further reasonably control the internal structure of concrete, reduce the degree of thermal shrinkage, and reduce the tendency of concrete to crack.
[0028] In a specific embodiment, the mass ratio of cement, expanded perlite and ceramsite is 4:1:3.5.
[0029] Appropriate aggregate particle size distribution helps to further ensure a stable concrete structure, reduce the amount of cement used, ensure concrete strength, and make concrete easier to process and construct.
[0030] Furthermore, the particle size of the expanded perlite is 1-5 mm; the particle size of the ceramsite is 1-10 mm; By combining aggregates of different particle sizes, the uniformity and density of concrete can be further maintained, and the strength and durability of concrete can be improved.
[0031] In a specific embodiment, the mass percentage of nano-silicon dioxide in the raw material system is 2%.
[0032] The addition of nano-silica can promote the hydration reaction of cement particles, form a dense gel structure, and improve the compressive and crack resistance of concrete. Nano-silica helps to fill the microscopic particles in concrete, thereby reducing the permeability of concrete and improving the durability of concrete. It can also reduce the amount of cement to a certain extent and reduce carbon emissions. Optionally, the particle size of nano-silica is 12~30nm.
[0033] The mass percentage of water reducer in the raw material system is 1.5%.
[0034] It can be understood that by further limiting the content of the water reducing agent, the water-cement ratio of the concrete can be significantly reduced, the fluidity and plasticity of the concrete can be improved, and the concrete can be made easier to process and pour without affecting the strength of the concrete.
[0035] Specifically, the water reducer is at least one of a polycarboxylate-based water reducer or a sulfonate-based water reducer. Among them, polycarboxylates have excellent dispersibility, promote the dispersion and coating of cement particles, thereby improving the strength and durability of concrete. Polycarboxylates can further reduce the friction between cement particles, reduce the internal friction resistance of concrete, thereby improving the crack resistance of concrete. It further controls the setting time of concrete and is more environmentally friendly and sustainable than traditional water reducers.
[0036] In a specific embodiment, the mass percentage of the stainless steel fiber in the raw material system is 2.5%, and the volume percentage is 0.5-1.5%.
[0037] By further limiting the content of stainless steel fiber, it is more conducive to the synergistic effect of carbon fiber and stainless steel fiber, further improving the fatigue resistance, impact resistance, tensile and bending resistance of concrete, further enhancing the ability of stainless steel fiber to resist cracks, and improving the crack resistance, corrosion resistance and easy processing of concrete.
[0038] In another specific embodiment, the mass percentage of the antifreeze agent in the raw material system is 0.5%.
[0039] By adopting the above technical solution, the frost resistance of concrete is improved, and at the same time, the corrosion effect on the concrete structure is relatively less. Compared with other antifreeze agents, the cost is lower.
[0040] Optionally, the antifreeze agent includes at least one of a calcium salt antifreeze agent, a silicate antifreeze agent, and a polycarboxylic acid antifreeze agent.
[0041] In a second aspect, the present invention provides a method for preparing crack-resistant concrete, which is used to prepare the crack-resistant concrete of the first aspect, comprising the following steps: (1) mixing a raw material system including cement, aggregate, nano-silicon dioxide, water, a water reducing agent, an antifreeze agent and stainless steel fiber to obtain a slurry concrete; (2) The slurry concrete is poured to obtain a slurry concrete layer, and a carbon fiber fabric is laid on the surface of the slurry concrete layer; the pouring and laying processes are repeated 2 to 3 times to obtain crack-resistant concrete.
[0042] Furthermore, the laying process also includes applying an adhesive to the surface of the carbon fiber fabric.
[0043] Optionally, the adhesive is epoxy resin.
[0044] Specifically, the preparation method of crack-resistant concrete comprises the following steps: (1) Dry mixing: using a mixer or other equipment to mix cement, lightweight aggregate, nano-silica and other dry powder materials according to the designed proportion to obtain a dry powder mixture.
[0045] (2) Wet mixing: Mix water, water reducer and antifreeze agent evenly, add pre-weighed water to the dry powder mixture according to the designed ratio, use a mixer or other equipment to mix evenly, ensure that the two are fully mixed to form a slurry concrete, and gradually add stainless steel fiber during the mixing process of the slurry concrete.
[0046] (3) Supplementary addition: add water reducer according to the designed ratio to adjust the fluidity of concrete and make it easier to construct. Add antifreeze agent to ensure that the concrete has good antifreeze performance in low temperature environment. Perform the final mixing of the entire concrete to ensure that all materials are fully mixed.
[0047] (4) Laying carbon fiber fabric, pouring bottom layer concrete, first pour a layer of concrete, the thickness is determined according to the design. Laying carbon fiber fabric, laying carbon fiber fabric on the surface of concrete that has not been fully hardened, ensuring that it is flat and wrinkle-free. Apply adhesive, apply epoxy resin or other adhesive on the surface of carbon fiber fabric to enhance the adhesion with concrete. Pour the upper layer of concrete, pour the second layer of concrete on the carbon fiber fabric, cover and compact it, and so on, laying 2-3 layers.
[0048] Optionally, the stirring speed in the mixing process in each step is 45-60 r / min, and the stirring time is 5-10 min.
[0049] Hereinafter, the anti-cracking concrete provided by the present invention is introduced in detail through specific embodiments.
[0050] Example 1
[0051] The anti-cracking concrete of this embodiment is composed of the following components: Water, cement, aggregate, water reducing agent, nano-silica, carbon fiber fabric, stainless steel fiber, antifreeze agent; Among them, cement is ordinary Portland cement, Southern Cement, PO 42.5; The aggregate is a compound of expanded perlite and ceramsite, with a density of 500kg / m 3 ; Expanded perlite, from commercial sources, particle size 1-5 mm Ceramic granules, from commercial sources, with a particle size of 1-10 mm, The water reducer is polycarboxylate water reducer, purchased from Zhongwei Hi-Tech, model: POLYFLEX TM 730; Among them, nano-silicon dioxide was purchased from DeLan Chemical, model: A200, particle size is 12nm; Carbon fiber fabric includes carbon fiber thread, which is made of 3000 carbon fibers twisted together; The carbon fiber fabric is a 2 / 1 twill structure; Carbon fiber is commercially available, model: T700SC-12000-50C, area density 300g / m 3 ; The stainless steel fiber was commercially available, NYCON-SSF, with a diameter of 0.2 mm and a fiber length of 38 mm; Among them, the antifreeze agent is a calcium salt antifreeze agent, which is commercially available.
[0052] The method for preparing crack-resistant concrete in this embodiment comprises the following steps: (1) Use a mixer or other equipment to mix 400kg cement, 150kg expanded perlite, 450kg ceramsite, 5kg nano-silicon dioxide and other dry powder materials according to the designed proportion, with a rotation speed of 45r / min and stirring for 20min to obtain a dry powder mixture; (2) Add 160 kg of water weighed in advance to the dry powder mixture and mix evenly using a mixer or other equipment at 60 r / min for 10 min to ensure that the two are fully mixed to form a slurry concrete; (3) During the mixing process of the slurry concrete, gradually add 20 kg of stainless steel fiber to ensure that it is evenly dispersed in the concrete. Continue stirring at 45 r / min for 10 minutes to ensure that it is evenly dispersed; (4) Add 4kg of water reducing agent to adjust the fluidity of the concrete to make it easier to construct. Add 4kg of antifreeze agent and perform a final mixing of the entire concrete at 45r / min for 10 minutes to ensure that all materials are fully mixed; (5) Laying carbon fiber fabric, pouring the bottom layer of concrete, first pouring a layer of concrete with a thickness of half the designed thickness; laying carbon fiber fabric, laying 1 layer of carbon fiber fabric on the surface of concrete that has not been fully hardened, ensuring that it is flat and wrinkle-free; applying adhesive, pouring the upper layer of concrete, pouring the second layer of concrete on the carbon fiber fabric, covering and compacting.
[0053] Example 2
[0054] The difference between this embodiment and embodiment 1 is that the area density of carbon fiber is 600g / m 3 ; In step (5), 2 layers of carbon fiber fabric are laid.
[0055] Example 3
[0056] The difference between this embodiment and embodiment 1 is that the area density of carbon fiber is 900g / m 3 ; In step (5), 3 layers of carbon fiber fabric are laid.
[0057] Example 4
[0058] The present embodiment is different from the embodiment 1 in that the diameter of the stainless steel fiber is 0.5 mm and the fiber length is 30 mm.
[0059] Example 5
[0060] The difference between this embodiment and embodiment 1 is that the length of the carbon fiber is 6 mm, the diameter is 10 μm, and the area density is 150 g / m 3 .
[0061] Example 6
[0062] The present embodiment is different from the embodiment 1 in that the carbon fiber fabric has a 1 / 4 twill structure.
[0063] Example 7
[0064] Compared with Example 1, the present embodiment is different in that the carbon fiber fabric has a satin structure.
[0065] Example 8
[0066] Compared with Example 1, the difference between this embodiment is that the added amount of cement is 380 kg, the added amount of expanded perlite is 130 kg, and the added amount of ceramsite is 470 kg.
[0067] Example 9
[0068] Compared with Example 1, the present embodiment is different in that the particle size of the expanded perlite is 8 mm.
[0069] Example 10
[0070] The difference between this embodiment and embodiment 1 is that the particle size of the ceramsite is 15 mm.
[0071] Comparative Example 1 The materials of this comparative example are ordinary C30 concrete, including: Water, cement, aggregate, water reducing agent.
[0072] Among them, cement is ordinary Portland cement, Southern cement, PO 42.5.
[0073] Among them, aggregate is a compound of sand and gravel.
[0074] Fine aggregate sand, sourced from the market, with a particle size of 0.1-1 mm; Coarse aggregate gravel, sourced from the market, with a particle size of 1-10 mm; The water reducer is polycarboxylate water reducer, purchased from Zhongwei Hi-Tech, model: POLYFLEX TM 730.
[0075] The preparation method of ordinary C30 concrete comprises the following steps: (1) Use a mixer or other equipment to mix 350 kg of cement, 700 kg of sand, 1100 kg of gravel and other dry powder materials according to the designed proportion, rotate at 45 r / min, and stir for 20 min to obtain a dry powder mixture.
[0076] (2) Add 175 kg of water weighed in advance to the dry powder mixture and mix evenly using a mixer or other equipment at 60 r / min for 10 min to ensure that the two are fully mixed to form a slurry concrete.
[0077] (3) Add 3.5 kg of water reducing agent to adjust the fluidity of the concrete to make it easier to construct; perform a final mixing of the entire concrete at 45 r / min for 10 minutes to ensure that all materials are fully mixed.
[0078] Comparative Example 2 The difference between this comparative example and comparative example 1 is that the amount of cement added is 400 kg, the amount of sand added is 650 kg, the amount of gravel added is 1150 kg, and the amount of water added is 160 kg.
[0079] Comparative Example 3 The difference between this comparative example and comparative example 1 is that the amount of cement added is 450 kg, the amount of sand added is 600 kg, the amount of gravel added is 1200 kg, and the amount of water added is 150 kg.
[0080] Comparative Example 4 The difference between this comparative example and Example 1 is that no carbon fiber fabric is added and step (5) is not performed.
[0081] Comparative Example 5 The difference between this comparative example and Example 1 is that no stainless steel fiber is added.
[0082] Comparative Example 6 The difference between this comparative example and Example 1 is that no nano silicon dioxide is added.
[0083] Comparative Example 7 The difference between this comparative example and Example 1 is that the amount of cement added is 300 kg and the amount of aggregate added is 400 kg.
[0084] Test Example 1 The concrete in the above examples and comparative examples were fully mixed and then loaded into test molds, weighed, placed and compacted. All samples were cured at 20±3° C. and 50% relative humidity for 24 hours and placed in a curing box for standard curing for 28 days.
[0085] The compression test was carried out according to GB / T50081-2019 "Concrete Physical and Mechanical Properties Test Method Standard". The specific test data of the experiment are shown in Table 1.
[0086] Table 1
[0087] According to the data comparison in Table 1, the addition of carbon fiber fabric can improve the compressive strength and tensile strength of concrete. The number of carbon fiber fabric layers helps to improve the compressive strength and tensile strength of concrete at 28 days. The appropriate proportion of lightweight aggregate added to concrete can reduce the amount of cement while maintaining the strength of concrete. The higher the tensile strength, the better the crack resistance.
[0088] The use of carbon fiber fabrics and stainless steel fibers can improve the compressive strength of concrete. When the fiber material content is about 2%, the compressive strength is increased by 33.3%. The fiber material is evenly distributed and randomly oriented, which prevents the generation and growth of microcracks and improves the crack resistance of concrete. The density of lightweight crack-resistant concrete is significantly lower than that of ordinary concrete, which reduces the deadweight of the structure. The addition of carbon fiber fabrics significantly improves the tensile strength by more than 100%. It makes up for the inherent defect of poor tensile performance of concrete and reduces the risk of cracking.
[0089] After adding carbon fiber fabric, the compressive strength of lightweight crack-resistant concrete is equivalent to or even higher than that of ordinary C50 concrete. While being lightweight, it can still maintain a high compressive strength. Carbon fiber fabric effectively inhibits the plastic shrinkage and drying shrinkage cracks of concrete. It significantly improves the crack resistance of concrete and extends the service life of the structure.
[0090] Comprehensive comparison shows that the crack-resistant concrete proposed by the present invention is lightweight, high-strength, high-toughness, excellent crack resistance and durability, and is suitable for projects with multi-function and high-performance requirements. Ordinary common concrete has a high density, average tensile strength, toughness and crack resistance, and is suitable for conventional construction projects.
[0091] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein by equivalents. If these modifications and variations fall within the scope of the claims of the present invention and their equivalent technologies, they should be considered to be within the protection scope of the present invention.
Claims
1. A crack-resistant concrete, characterized in that: The raw material system of the anti-cracking concrete includes, by mass, 160-200 parts of water, 350-500 parts of cement, 600-800 parts of aggregate, 3.5-6 parts of water reducer, 3.5-7 parts of nano silicon dioxide, 10-20 parts of carbon fiber fabric, 15-30 parts of stainless steel fiber and 3.5-7 parts of antifreeze agent; the density of the aggregate is 340-690 kg / m 3 .
2. The crack-resistant concrete according to claim 1, characterized in that: The carbon fiber fabric has 1 to 3 layers; and / or, The carbon fiber fabric comprises carbon fiber threads, wherein the carbon fiber threads are twisted together from 2000 to 4000 carbon fibers; and / or, The length of the stainless steel fiber is 20-50 mm, and the diameter is 0.2-0.3 mm.
3. The crack-resistant concrete according to claim 2, characterized in that: The carbon fiber fabric has a twill structure; and / or, The carbon fiber has a length of 9-12 mm, a diameter of 7-10 μm, and an area density of 300-900 g / m 3 .
4. The crack-resistant concrete according to claim 3, characterized in that: The carbon fiber fabric has a 2 / 1 twill structure.
5. The crack-resistant concrete according to claim 1, characterized in that: The aggregate includes expanded perlite and ceramsite; the mass ratio of the expanded perlite to the ceramsite is (30-50): (50-70).
6. The crack-resistant concrete according to claim 5, characterized in that: The mass ratio of the cement, the expanded perlite and the ceramsite is 4:1:3.5; and / or, The mass percentage of the nano silicon dioxide in the raw material system is 2%; and / or, The mass percentage of the water reducing agent in the raw material system is 1.5%; and / or, The mass percentage of the stainless steel fiber in the raw material system is 2.5%, and the volume percentage is 0.5-1.5%; and / or, The mass percentage of the antifreeze agent in the raw material system is 0.5%.
7. The crack-resistant concrete according to claim 6, characterized in that: The particle size of the expanded perlite is 1-5 mm; and / or, The particle size of the ceramsite is 1-10 mm; and / or, The particle size of the nano silicon dioxide is 12-30 nm.
8. The crack-resistant concrete according to any one of claims 1 to 7, characterized in that: The water reducer comprises at least one of a polycarboxylate-based water reducer or a sulfonate-based water reducer; and / or, The antifreeze agent includes at least one of a calcium salt antifreeze agent, a silicate antifreeze agent or a polycarboxylic acid antifreeze agent.
9. A method for preparing crack-resistant concrete, for preparing the crack-resistant concrete according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) mixing a raw material system including cement, aggregate, nano-silicon dioxide, water, a water reducing agent, an antifreeze agent and stainless steel fiber to obtain a slurry concrete; (2) The slurry concrete is poured to obtain a slurry concrete layer, and a carbon fiber fabric is laid on the surface of the slurry concrete layer; the pouring and laying processes are repeated 1 to 3 times to obtain the crack-resistant concrete.
10. The method for preparing crack-resistant concrete according to claim 9, characterized in that: The laying process also includes applying an adhesive to the surface of the carbon fiber fabric.
Citation Information
Patent Citations
Lightweight thermal insulation concrete slab and preparation technology thereof
CN109650791A
Self-compacting fiber toughened lightweight aggregate concrete and preparation method thereof
CN109776052A